Constructing a fertility model and analyzing its relation to female labour force participation - Abu Bakar, Nor'Aznin; Abdullah, Norehan; Abdullah, Hussin (Universiti Utara Malaysia, 2012)
This study tends to investigate the ambiguous relationship between fertility and women’s labour force participation in the case of Malaysia and other selected Asian countries such as Singapore, Thailand, Indonesia, the Philippines and Vietnam. Using a panel of observations for the period 1995 to 2009, this study examines the correlation and the causality effect between fertility rate and female labour force participation; and finally, tries to construct a fertility model by identifying the determinants of fertility based on the long-run and the short-run analysis.This study found that there is mixed correlation between the regression variables in ASEAN countries but none of them have a strong correlation.The highest positive correlation is between health expenditure (he) and life expectancy at birth, while a negative correlation is found between health expenditure (he) and self-employed – female. The results on causality tests shows that primary education, health expenditure, life expectancy at birth, labour participation rate, and self-employed-female do not granger-cause fertility rate in all six ASEAN countries.However there is a unidirectional causality which runs from fertility rate to education primary, life expectancy at birth and labour participation rate.The PMG, MG and DFE (the panel ARDL) tests show that the three variables; life expectancy (le), education primary (ep) and labour force participation (lp) are statistically significant in influencing fertility rate in the long run.At the same time, the self-employed female (se) and health expenditure (he) are also statistically significant with lower value of 0.253 and -2,030 respectively.In the short run all variables are statistically significant and affect the fertility rate except the health expenditure.